Psychological leadership training of crisis management - Лефтеров, Василь Олександрович; Лефтеров, В. О.; Лефтеров, Василий Александрович; Lefterov, Vasyl O.; Лазор, Катерина Петрівна; Лазор, К. П.; Лазор, Екатерина Петровна; Lazor, Kateryna P. (Faculty of Philosophy and Psychology of YSU, 2019)
Psychological aspects of management performance are being considered. The necessity of delivering psychological bases of crisis management to leadership is substantiated and psychological recommendations for effective management of leaders have been offered. The author’s vision of the socio-psychological components of the managerial competence of a modern manager is being highlighted: it suggests the introduction into the system of training managers of various categories of psychological training as an innovative technology of forming leaders’ practical skills and capabilities of efficient personnel management. The results of an experimental study of the influence of training on the dynamics of personal and professionally significant qualities of leaders are being presented. A significant positive impact of leadership training on the personal sphere of leaders, increasing of leadership potential and the development of individual psychological qualities that are essential for a modern manager, has been established. Over time, after the training, the level of volitional, leadership qualities has been increased, such as leadership role, self-discipline, purposefulness, and the assessment of their business and personal qualities given by subordinates increases. Psychological training of leadership in the form of training contributes to the development of such necessary qualities of crisis management as stress resistance and the ability for emotional self-regulating.

Розглядаються психологічні аспекти ефективності управління. Обґрунтовано необхідність надання психологічного базису антикризового управління керівництву та запропоновано психологічні рекомендації щодо ефективного управління лідерами. Висвітлено авторське бачення соціально-психологічних складових управлінської компетентності сучасного менеджера, пропонується впровадження в систему підготовки менеджерів різних категорій психологічного тренінгу як інноваційної технології формування практичних навичок та можливостей лідерів ефективного управління персоналом. Представлені результати експериментального дослідження впливу тренінгу на динаміку особистісних та професійно значущих якостей лідерів. Встановлено суттєвий позитивний вплив навчання лідерських якостей на особисту сферу лідерів, збільшення лідерського потенціалу та розвиток індивідуально-психологічних якостей, необхідних для сучасного менеджера. З часом після тренінгу підвищується рівень вольових, лідерських якостей, таких як керівна роль, самодисципліна, цілеспрямованість та оцінка їх ділових та особистих якостей, яку дають підлеглі. Психологічний тренінг лідерства у формі тренінгу сприяє розвитку таких необхідних якостей антикризового управління, як стресостійкість та здатність до емоційної саморегуляції.

Рассматриваются психологические аспекты эффективности управления. Обоснована необходимость предоставления психологического базиса антикризисного управления руководству и предложены психологические рекомендации по эффективному управлению лидерами. Освещены авторское видение социально-психологических составляющих управленческой компетентности современного менеджера, предлагается внедрение в систему подготовки менеджеров различных категорий психологического тренинга как инновационной технологии формирования практических навыков и возможностей лидеров эффективного управления персоналом. Представлены результаты экспериментального исследования влияния тренинга на динамику личностных и профессионально значимых качеств лидеров. Установлено существенное положительное влияние обучения лидерских качеств на личную сферу лидеров, увеличение лидерского потенциала и развитие индивидуально-психологических качеств, необходимых для современного менеджера. Со временем после тренинга повышается уровень волевых, лидерских качеств, таких как руководящая роль, самодисциплина, целеустремленность и оценка их деловых и личных качеств, которую дают подчиненные. Психологический тренинг лидерства в форме тренинга способствует развитию таких необходимых качеств антикризисного управления, как стрессоустойчивость и способность к эмоциональной саморегуляции.
Lefterov V. O. Psychological leadership training of crisis management / V. O. Lefterov, K. P. Lazor // Actual Psychology. – V. 2 (4). – Faculty of Philosophy and Psychology of YSU, 2019. – P. 36-42.
Keywords: psychological training; crisis management; social and psychological components of a successful leader; психологічний тренінг; антикризове управління; соціальна та психологічна складові успішного керівника; психологический тренинг; антикризисное управление; социально-психологические составляющие успешного лидера; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology